Genome wide investigation of papillary thyroid carcinoma - Finn, Stephen (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2005)
In recent years, there has been a technological explosion in the fields of molecular pathology and molecular oncology. The genome, transcriptome and increasingly the proteome of diverse tumours can now be analysed in minute detail. Thyroid cancer has come to the forefront of molecular pathology as a result of the sad consequences of the Chernobyl disaster and the recognition of the role of retmutations in familial and sporadic medullary thyroid carcinoma and ret/PTC rearrangements in papillary thyroid carcinoma.
Keywords: Health Sciences, Ph.D.; Ph.D. Trinity College Dublin